Light‐Triggered RNA Annealing by an RNA Chaperone1. Issue 25 (8th May 2015) - Panja, Subrata; Paul, Rakesh; Greenberg, Marc M.; Woodson, Sarah A.
Abstract Non‐coding antisense RNAs regulate bacterial genes in response to nutrition or environmental stress, and can be engineered for artificial gene control. The RNA chaperone Hfq accelerates antisense pairing between non‐coding RNAs and their mRNA targets, by a mechanism still unknown. We used a photocaged guanosine derivative in an RNA oligonucleotide to temporally control Hfq catalyzed annealing. Using a fluorescent molecular beacon as a reporter, we observed RNA duplex formation within 15 s following irradiation (3 s) of photocaged RNA complexed with Hfq. The results showed that the Hfq chaperone directly stabilizes the initiation of RNA base pairs, and suggests a strategy for light‐activated control of gene expression by non‐coding RNAs.